Keabsahan Jual Beli Benda Virtual Melalui Sistem Gacha Dalam Game Online - Rayhan Diokabilla Soewandi; Eko Rial Nugroho (Fakultas Hukum Universitas Islam Indonesia, 2024)
Many companies are currently trying to create games, both online and offline games because technology is developing very rapidly. These games also provide a purchase system in them. An example is a transaction to buy digital goods in a game using the gacha system. Gacha itself is a form of monetization strategy. The gacha system in this game includes various characters and certain items that players can obtain through this mechanism. This mechanism is carried out by players spinning or withdrawing gacha using game currency and then the results will be given randomly. So this research aims to analyze whether buying and selling in the game meets the buying and selling requirements in the Civil Code and to analyze how legal protection is when buyers make purchases using the in-game gacha system. Basically, a contract must be based on the agreement of the parties entering into the agreement and there is an element of uncertainty in the practice of buying and selling with this system. For these reasons, the author in this study chose the title